1977
DOI: 10.1104/pp.59.5.808
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Light Level, Sucrose Concentration, and Translocation of Carbon 11 in Zea mays Leaves

Abstract: The mechanism of carbon transport in Zea mays leaves was investigated using carbon 11 which is a short lved (half-lfe 20.4 min) positronemitting isotope. The gamma radiation produced on annihilation allows in vivo or nondestructive measurement of the isotope and the short halflife allows many measurements of trandocation to be made on the same leaf within the same day.Carbon 11 produced by the 10B (d,n)"C nuclear reaction was converted to "CO2, fed to a leaf as a short pulse, and assimilated during photosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
22
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…The "C isotope of carbon was used as the tracer to allow in vivo detection of carbon movement within the plant and repetitive "CO2 feeds of the same leaf over time (17). The experimental design was as described by Woodrow et al (22).…”
Section: "Co2 Labeling and Speed Of Assimilate Movementmentioning
confidence: 99%
“…The "C isotope of carbon was used as the tracer to allow in vivo detection of carbon movement within the plant and repetitive "CO2 feeds of the same leaf over time (17). The experimental design was as described by Woodrow et al (22).…”
Section: "Co2 Labeling and Speed Of Assimilate Movementmentioning
confidence: 99%
“…The lower flux rate for sucrose derived from fructose compared to sucrose supplied directly as attributed to a limitation in the rate of sucrose synthesis. Recent studies have demonstrated the dependence of translocation rate upon sucrose concentration in leaves (24).…”
mentioning
confidence: 99%
“…The sugar supply of non-chlorophyllous tissues varies depending upon factors which affect the efficiency ofcarbon fixation by leaves and transport of the recently synthesized carbohydrates (5,7,13,21).…”
mentioning
confidence: 99%